2012
DOI: 10.1542/peds.2012-1671
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Childhood Obstructive Sleep Apnea Syndrome

Abstract: OBJECTIVES: This revised clinical practice guideline, intended for use by primary care clinicians, provides recommendations for the diagnosis and management of the obstructive sleep apnea syndrome (OSAS) in children and adolescents. This practice guideline focuses on uncomplicated childhood OSAS, that is, OSAS associated with adenotonsillar hypertrophy and/or obesity in an otherwise healthy child who is being treated in the primary care setting. METHODS:Of 3166 articles from 1999-2010, 350 provided relevant da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
668
1
21

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,544 publications
(752 citation statements)
references
References 19 publications
16
668
1
21
Order By: Relevance
“…This was the case even when controlling for neighborhood income, BMI, and adenotonsillectomy, factors that have previously been associated with OSA in young children. 18,34 This finding parallels previous research showing increased OSA symptoms (ie, snoring and sleep-disordered breathing) among Black children relative to White children. [18][19][20] Seasonal allergies and asthma have been shown to increase risk for OSA 16 ; however, rates of these risk factors did not differ by race in this sample.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…This was the case even when controlling for neighborhood income, BMI, and adenotonsillectomy, factors that have previously been associated with OSA in young children. 18,34 This finding parallels previous research showing increased OSA symptoms (ie, snoring and sleep-disordered breathing) among Black children relative to White children. [18][19][20] Seasonal allergies and asthma have been shown to increase risk for OSA 16 ; however, rates of these risk factors did not differ by race in this sample.…”
supporting
confidence: 84%
“…Identifying these genetic factors, and how they may interact with environmental effects to produce OSA onset in early childhood is especially important given the broad developmental risks that OSA poses to young children. 26,27,34 Further, despite Black preschoolers having sleep patterns similar to those of White children in this sample, a greater proportion of White children presented for difficulty falling/ staying asleep concerns and were given a diagnosis of pediatric insomnia. This difference was present even when we controlled for caregiver-child bed-sharing.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…However, a clinically optimal predictive model that included other known demographic risk factors could not be determined. These study findings are important, as they demonstrate that PSG reliably provides information that can help clinicians prepare for potential adverse events related to postoperative respiratory recovery, but the decision to admit patients postoperatively for monitoring should also include physician clinical judgment based on the patient's other risk factors and social situations.The literature and recent guidelines have been more consistent in their recommendations for postoperative overnight monitoring based on demographic risk factors rather than OSAS 2,3,5,10,13,14,18,19,[25][26][27][28][29] Specifically, both AAP and AAO-HNSF guidelines agree that children should be admitted postoperatively if they have high-risk factors including age <3 years, obesity, and/or various comorbidities. 2,3,5,10,13,14,18 In the current study, only some demographic characteristics were found to be significantly associated with adverse major respiratory events (age <3 years and presence of FTT [regardless of age]), but we did not find this to be true for children who had a history of prematurity, other comorbidities, or obesity.…”
mentioning
confidence: 99%